PENGARUH PENGEMBANGAN SUMBER DAYA APARATUR TERHADAP KUALITAS PELAYANAN PUBLIK PADA KANTOR KECAMATAN SEI KUNJANG KOTA SAMARINDA - ., Herlina (PREDIKSI, 2014)
The INFLUENCE of RESOURCE DEVELOPMENT APPARATUS TOWARDS the QUALITY of PUBLIC SERVICES at the DISTRICT OFFICES of SEI KUNJANG, SAMARINDA CITY under the guidance of Mr. Suhardiman, s. Sos., M.Si and Mr. Drs. Peace Darmadi, M.Si Goal of this research is to know the influence of resource development apparatus towards improving the quality of public services at the District offices of Sei Kunjang Samarinda.Research methods used in this research is quantitative research approach to indicator development resources Apparatus (X), which consists of; a. education and training, work placements, b. c. Coaching career, d. Increased level of formal education, employee discipline Enforcement, e., f. mutation and promotion. Indicators of the quality of public services (Y), namely; a. the time of service, attitude and behavior of b. c. responsibility in service, Service Procedures, d. e. Convenience in obtaining service, f. Ease in obtaining services. Data analysis tools that are used in this research is a simple linear regression test.Regression test results Data linaer go out to count the value of R that amounted to 0,934 (positive values). While the value of R table against a sample of 28 respondents obtained value table of 0,381 Means R R count greater than R chart, it clarify that there is a positive influence.Â Â To find out if they are also positive influence significant influence occurred, namely by looking at the column's significance. Said to be of significance when significant values below or equal to 0.05, apparently the column values the significance of 0000 means there is a significant influence.Based on the above test results describes the accepted that there is a Hypothesis that the influence of resource development Apparatus towards the quality of public services at the District offices of Sei Kunjang Samarinda.Â To find out the percentage of the influence of variables X resource development Apparatus variable Y of quality public service can be seen on rated R Square (the coefficient of diterminasi) of variable meaning 0,873 resource development Apparatus towards the quality of public services at the District offices of Samarinda Sei Kunjang Samarinda of 87,3%, meaning there was only 12.7 percent of the roles of the other variables that are not examined in this study.